Human papillomavirus detection in dysplastic and malignant oral verrucous lesions. Issue 3 (15th December 2011) - Stokes, Angela; Guerra, Eliete; Bible, Jon; Halligan, Eugene; Orchard, Guy; Odell, Edward; Thavaraj, Selvam
Abstract : The role of human papillomaviruses (HPV) in dysplastic and malignant oral verrucous lesions is controversial since there is a wide range in the incidence of virus detection. This study used a multi-tiered method of HPV detection using DNA in-situ hybridisation (ISH) for low- and high-risk subtypes, consensus PCR, and HPV genotype analysis in archival tissue from 20 cases of dysplastic and malignant oral verrucous lesions. The biological significance of HPV DNA detection was assessed by p16 immunohistochemistry (IHC). While 1/7 carcinomas and 5/13 dysplasias contained HPV DNA by consensus PCR and genotype analysis, all specimens were negative for low- and high-risk HPV ISH and negative for p16 IHC. Results show that although high-risk HPV DNA is detectable in a subset of these lesions, the lack of p16 overexpression suggests that the oncogenic process is not driven by HPV oncoproteins.